UOT OF DENTISTS-ORTHOPEADISTS WORK OVER IMPLANTOLOGIC RECEPTION. REMOVABLE AND CONDITIONALLY REMOVABLE CONSTRUCTIONS - E.V. Diiev; T. V. Diieva; V. V Lepsky; V. V. Lepsky; V. A. Labunets (Український стоматологічний альманах, 2017)
Complete removable and conditionally removable dentures with implant fixation have a wide variety of application within the public health in our country. However, unlike traditional methods of patients’ prosthesis with complete edentia, methods of dental implantation in Ukraine do not have full legal status because of the lack of clinical technological protocols and complete lack of departmental time standards for doctors- orthopedists on their production.